The Specialized Educational Service - AEE, affectivity and the contribution of the institutional neuropsychopedagogue on the Autistic Spectrum Disorder (International Seven Journal of Multidisciplinary, 2023)
Currently, the recognition of the AEE - Specialized Educational Service, as an inclusive educational practice, whose remarkable presentation of evolution, is directly related to the management of ASD - Autistic Spectrum Disorder. Therefore, the reality about the student's autonomy, from cognitive-behavioral interventions, is feasible. Thus, the recognition of the AEE - Specialized Educational Service as an effective educational practice has been solidified, and one of the fields where this is verified is in the treatment of autistic students in schools that provide such service. The continuous scientific educational effort of educational professionals and researchers has produced numerous tools to help users of these modalities. The objective of this work is, based on the scientific literature of renowned authors, to identify what is conceptualized as Autism Spectrum Disorder - ASD and the most effective educational conducts and techniques in the school space. Given the advancement of research on AEE - Specialized Educational Service, both by professionals in this area and researchers, the objectives of this work are to search for the study proposals on autism in scientific articles, to assess whether the cognitive and behavioral technical studies are effective in treating the Autism Spectrum Disorder - ASD, and thus be able to promote an evaluation of the most appropriate strategies to be used in schools with the contribution of the institutional neuropsychopedagogist in identifying specific needs and referrals to other specialists.